A biased opinion: Demonstration of cognitive bias on a fingerprint matching task through knowledge of DNA test results. (July 2017) - Stevenage, Sarah V.; Bennett, Alice
Highlights: Results of DNA tests can provide contextual information that triggers cognitive bias in fingerprint analysis. Cognitive bias could be demonstrated in both 'match' and 'mismatch' decisions. Cognitive bias is greater when the task is made harder through time pressure. A process approach is provided which identifies risks and solutions for each stage of analysis. Abstract: One study is presented which explores the biasing effects of irrelevant contextual information on a fingerprint matching task. Bias was introduced by providing the outcomes of a DNA test relating to each fictitious case under consideration. This was engineered to suggest either a match, no match, or an inconclusive outcome, and was thus either consistent, misleading or unbiased depending on the ground truth of each fingerprint pair. The results suggested that, when the difficulty of the fingerprint matching task was measurably increased, participants became more vulnerable to the biasing information. Under such conditions, when performance was good, misleading evidence lowered accuracy, and when performance was weaker, consistent evidence improved accuracy. As such, the results confirmed existing demonstrations of cognitive bias from contextual information in the fingerprint task. Moreover, by taking a process-based approach, it became possible to articulate the concerns, and the potential solutions, at each stage of the workflow. The results offer value for the forensic science community in extending the evidence-base regarding cognitive bias, and in articulating routes to improve the credibility of fingerprint decisions.